Factors Related to the Incidence of ICU-acquired Infections in Iran: Analysis of National Data - Neda IZADI; Yadollah MEHRABI; Koorosh ETEMAD; Babak ESHRATI; Seyed-Saeed HASHEMI-NAZARI (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
Introduction: Patients admitted to intensive care units (ICUs) are particularly susceptible to hospital-acquired infections (HAIs). This study aimed to investigate factors related to the incidence of ICU-AIs in Iran. Materials and Methods: In this study, Iranian nosocomial infections surveillance and hospital statistics and information system were used to collect data on patients with HAIs in 2018. The data was expanded based on 12 months of the year (13,632 records in terms of “hospital-ward-month”) and then, the last observation carried forward method was used to replace the missing data. The generalized negative binomial regression with “patient-days” as an offset variable was used to identify the factors affecting the incidence of ICU-AIs. Results: Of the patients 22.92%, 5.76%, 13.62%, 43.41%, and 14.29% of were in neonatal ICU, pediatric ICU (PICU), internal ICU, general ICU, and surgical ICU (SICU), respectively. The most common ICU-AIs were ventilator-associated events (VAE) and urinary catheter-related infections (UTI). Based on multivariable regression, the number of death [incidence rate ratio (IRR)=1.02], the number of device-related infections (IRR=1.1), ward type [PICU (IRR=1.58), internal ICU (IRR=1.63), general ICU (IRR=1.53) and SICU (IRR=1.47)], bed occupancy rate indicator (IRR=1.17 for moderate conditions), hospital’s accreditation (IRR=1.23 and IRR=1.73 for accreditation 1 and 2, respectively) and hospital’s expertise were associated with an increase in ICU-AIs incidence. Conclusion: Based on the results, the most common ICU-AIs were VAE and UTI. Therefore, to reduce incidence of ICU-AIs, full hygiene control should be performed by the medical staff. Ventilators and catheters should be used in special circumstances with minimum duration.